Filia e Agape - Olivetti, Bernardo (Medicina e Morale, 1987)
'Where there is love for man, there is also love for art' is the well-known Hippocratic expression often quoted by medical historians as proof of the high ethical level reached by the Master of Things and his school with limpid clarity, and more generally of the subtle spirituality developed by the Greeks to which we are all indebted.